2017
DOI: 10.1038/srep40872
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Modulation of Urinary Bladder Contraction for Lower Urinary Tract Dysfunction

Abstract: As current clinical approaches for lower urinary tract (LUT) dysfunction such as pharmacological and electrical stimulation treatments lack target specificity, thus resulting in suboptimal outcomes with various side effects, a better treatment modality with spatial and temporal target-specificity is necessary. In this study, we delivered optogenetic membrane proteins, such as channelrhodopsin-2 (ChR2) and halorhodopsin (NpHR), to bladder smooth muscle cells (SMCs) of mice using either the Cre-loxp transgenic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…By way of compensation, the DAPM offers the potential to visualize bladder and urethra movements, which can be video captured allowing relation of electrophysiology to the bladder movement . The potential to combine with bladder sheet and Ca 2+ imaging experiments or optogenetic approaches might bring new insights to the relationship of urothelial transmitters and central nervous system activity.…”
Section: Discussionmentioning
confidence: 99%
“…By way of compensation, the DAPM offers the potential to visualize bladder and urethra movements, which can be video captured allowing relation of electrophysiology to the bladder movement . The potential to combine with bladder sheet and Ca 2+ imaging experiments or optogenetic approaches might bring new insights to the relationship of urothelial transmitters and central nervous system activity.…”
Section: Discussionmentioning
confidence: 99%
“…Depolarization of smooth muscle cells expressing ChR2 by blue light induces vasoconstriction in brain of SM22-ChR2 mice. Recently, it has been reported that contraction of bladder smooth muscles and cardiovascular smooth muscles can be regulated by ChR2 [29,30]. So, we used ChR2 mice to control cerebral vasoconstriction in vivo through optical light stimulation.…”
Section: In Vivo Animal Preparation and Imaging For Optical Activatiomentioning
confidence: 99%
“…Expression of ChR2 in the CNS has been used to study a number of behaviors, including those related to anxiety, learning, and depression (Huber et al, 2008 ; Covington et al, 2010 ; Tye et al, 2011 ). Recently, optogenetic modulation of bladder smooth muscle was shown to elicit voiding in vivo (Park et al, 2017 ), and our group demonstrated that inhibition of sensory afferent activity via archaerhodopsin, a light-activated proton pump, attenuates pain-related behavior in the context of bladder inflammation (Samineni et al, 2017a ). The present study is an important addition that demonstrates for the first time the effects of direct, selective neuronal activation of distinct bladder afferents on behavioral correlates of bladder sensation and function.…”
Section: Discussionmentioning
confidence: 99%